Harmonization of ASEAN Policy in Responding to the Phenomenon of Migration and Prevention of Transnational Crime - Felix Ferdin Bakker; Respati Triana Putri; Ale Alfero Deputra (Journal of Law and Border Protection, 2022)
The existence of migration and technological developments at present make the boundaries between countries even more invisible. ASEAN's position in Southeast Asia is becoming increasingly problematic. Currently, the development of crimes in the Southeast Asian region which is increasingly widespread makes it necessary to strengthen cooperation between countries through the ASEAN organization. Until now, the ASEAN Ministerial Meeting on Transnational Crimes (AMMTC) has not been able to equalize perceptions between ASEAN countries in formulating policies. This research itself is based on these problems with research based on juridical normative research methods. Normative legal research is also called doctrinal legal research, library research, or documentary studies. It is hoped that with an organization that brings together elements of border and security in ASEAN, policies can be more focused. Besides, Indonesia's position as a large country in ASEAN is also required to play a more active role in solving this problem.